A comparative study of thulium laser resection of the prostate and bipolar transurethral plasmakinetic prostatectomy for treating benign prostatic hyperplasia. (29th October 2012) - Peng, Bo; Wang, Guang‐chun; Zheng, Jun‐hua; Xia, Sheng‐qiang; Geng, Jiang; Che, Jian‐ping; Yan, Yang; Huang, Jian‐hua; Xu, Yun‐Fei; Yang, Bin
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? Thulium laser is a new generation of surgical laser. It is a minimally invasive technology with several advantages, including rapid vaporization and minimal tissue damage and bleeding. However, details regarding the safety and efficacy of thulium laser in treating BPH remains unknown. We performed a comparative study in 100 patients with BPH of the safety and efficacy of thulium laser resection of the prostate (TMLRP, n = 50) and bipolar transurethral plasmakinetic prostatectomy (TUPKP, n = 50). We found that the efficacy and indications were the same in TMLRP and TUPKP. In TUPKP, the morbidity of urethrostenosis was low, and was nearly bloodless in surgery and had higher safety. Nevertheless, TUPKP is more suitable for patients with larger prostate volume. Objective To compare the safety and short‐term efficacy of thulium laser resection of the prostate (TMLRP) and bipolar transurethral plasmakinetic prostatectomy (TUPKP) for the treatment of patients with benign prostatic hyperplasia (BPH). Methods A total of l00 patients diagnosed with BPH were randomly divided into two groups, treated with either TMLRP (50, group 1) or TUPKP (50, group 2). There was no significant difference in preoperative variables such as age, prostate volume, prostate‐specific antigen (PSA) level, International Prostate Symptom Score (IPSS), maximum urinary flow rate (Qmax) and postvoid residual urine volume (PVR) between the two groups. The perioperative parameters and therapeutic effects were recorded and compared between the two groups. Results There were significant differences in the following parameters between the two groups (TMLRP vs TUPKP [mean ± SD]): operation duration, 61.2 ± 24.2 vs 30.14 ± 15.9 min; catheterization time, 1.8 ± 0.4 vs 3.2 ± 0.6 d; postoperative hospital stay, 3.3 ± 0.8 vs 4.1 ± 1.3 d. The volume of blood loss and postoperative bladder irrigation were significantly lower in TMLRP group than in the TUPKP group. At 1 month after the operation, there were four cases of urethral stricture in the TUPKP group. At 3 months after the operation, IPSS, quality of life (QoL), Qmax and PVR were significantly improved, with no significant difference between the two groups. Conclusions TMLRP is superior to TUPKP in terms of safety, blood loss, recovery time and complication rate, and is as efficacious as TUPKP for treating BPH. Operation duration was significantly longer in the TMLRP group than in the TUPKP group.